The degree to which students of the Faculty of Education at the University of Zakhoemploy habits of mind in their university life (Numerus academy review, 2026)
The degree of employment of students of the Education's Faculty at the University ofZakho to habits of the mind in their university life. The aim of the research is to find out the degree to which students of the Faculty ofEducation at the University of Zakho employ the habits of the mind in their university life, by monitoring the opinions of a sample of students of the College of Education at theUniversity of Zakho, and a questionnaire was designed consisting of (55) paragraphs distributed over ten axes, namely: (perseverance - control To recklessly - to listen withunderstanding and empathy - to think flexibly - to self-organize - to strive for accuracy -to question and to ask problems - to apply previous knowledge to new situations - tovisualize, innovate and renew - permanent and continuous learning.), Was applied to a random sample of (115) students with a ratio 20% of the original research community, and the researcher reached several results Including:-Most students employ mental habits in their university life to a small degree, and the most common mental habits used for them are: applying their previous knowledge to newsituations, thinking flexibly, while they employ mental habits related to perception,innovation, innovation, self-regulation, and the struggle for accuracy in a very smalldegree.-There were no statistically significant differences between the averages of the students scores in the overall degree of the scale according to the variable of gender, specializationand school stage, while some differences were found between the averages of the students’ scores on some of the points of the scale, and with varying degrees.